Pursuing the stabilisation of crystalline nanostructured magnetic manganites through a green low temperature hydrothermal synthesis. Issue 13 (21st March 2017) - Minelli, A.; Dolcet, P.; Diodati, S.; Gardonio, S.; Innocenti, C.; Badocco, D.; Gialanella, S.; Pastore, P.; Pandolfo, L.; Caneschi, A.; Trapananti, A.; Gross, S.
Abstract : A quick, easy and green water-based synthesis protocol involving coprecipitation of oxalates combined with hydrothermal treatment resulted in the crystallisation of nanostructured manganites at a relatively low temperature (180 °C). Abstract : A quick, easy and green water-based synthesis protocol involving coprecipitation of oxalates combined with hydrothermal treatment resulted in the crystallisation of nanostructured manganites at a relatively low temperature (180 °C). The subcritical hydrothermal approach was shown to play a key role in stabilising phases which are generally achieved at much higher temperatures and under harsher conditions, thus disclosing an exciting alternative for their synthesis. Through this mild wet chemistry approach, the compounds CuMnO2, ZnMn2 O4 and ZnMnO3 were synthesised as nanocrystalline powders. Noticeably, the optimised route proved to be effective in stabilising the exotic polymorph cubic spinel ZnMnO3 in pure form. This is particularly notable, as very few records concerning this compound are available in the literature. The compounds were fully characterised from compositional, structural, morphological and magnetic points of view.